(untitled) (Journal of Society of Surgeons of Nepal, 2020)
Introduction: Advances in laparoscopy has replaced many conventional open surgeries; hepatic cystic echinococcosis (CE) surgery is no exception. This study aims to evaluate the feasibility, postoperative outcomes including complications and recurrence rates after employing laparoscopic treatment for hepatic CE. Methods: This is a prospective study involving patients who underwent laparoscopic intervention for Hepatic CE at Nepal Medical College and Teaching Hospital from 1st July 2014 to 30th June 2019. Laparoscopic partial pericystectomy was done through the Palanivelu hydatid system and technique after pretreatment with albendazole (10mg/kg) for at least one week. Clavien-Dindo classification was used to classify postoperative complications. Results: Twenty-two patients were enrolled in the study with a mean age of 33.95±15.24 (18.0-75.0) years, 15 (68.18%) of them being female. Abdominal pain (77.3%) was the commonest complaint and a single cyst in the right lobe of the liver was the commonest pathology. The mean size of the cyst was 10.2±3.0 (5.0-15.0) cms. 40.9% of the cysts belonged to WHO-IWGE Grade CE3, while grade CE2 and CE1 consisted of 27.3% each. The mean operation time was 80.7 ± 19.7 (60-120) minutes. Out of the 22 patients, six (27.3%) had minor grades while four (18.2%) had major grades of Clavien-Dindo complications. Among the major complications, one (4.5%) patient each developed biliary fistula managed with ERCP and stenting, recurrence after three months, intraoperative bleeding requiring conversion to open surgery, and acute kidney injury managed with dialysis. There was no anaphylaxis or operative mortality. Conclusion: In selected patients, laparoscopic treatment for hepatic CE is feasible even in a resource-limited country like Nepal. With a low rate of conversion, recurrence and mortality, laparoscopic management can be safe, effective and encouraging treatment modality for the patients of hepatic CE.